Men and dogsled navigating large sled with sail on Windy Arm, Tagish Lake, ca. 1898 - Curtis, Asahel, 1874-1941 (1898)
Caption on image: Curtis 663 Handwritten on verso: Windy Arm. PH Coll 519.663 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number